Growth Performance and Enzymatic Response of the Grasshopper, Calliptamus abbreviatus (Orthoptera: Acrididae), to Six Plant-Derived Compounds. Issue 3 (5th June 2020) - Wang, Yueyue; Huang, Xunbing; Chang, Babar Hussain; Zhang, Zehua
Abstract: Plant-derived compounds are sources of biopesticides for the control of insect pests. We compared the growth performance and enzymatic response of the grasshopper Calliptamus abbreviatus Ikonn to six plant-derived compounds (rutin, quercetin, nicotine, matrine, azadirachtin, and rotenone) in laboratory and field trials. When exposed to the six compounds, C. abbreviatus had significantly reduced growth and survival. All the compounds significantly induced an elevated level of reactive oxygen species, indicating oxidative damage. The activity of detoxifying enzymes, including cytochrome P450s, carboxylesterase, glutathione- S -transferase, and UDP-glucuronosyltransferase, and the antioxidant enzymes, including superoxide dismutase, catalase, and peroxidase, all significantly increased after exposure to the six compounds. These data suggest that the six plant-derived compounds had negative effects on C. abbreviatus . Of the six compounds, matrine, azadirachtin, and rotenone were more toxic to C. abbreviatus, followed by nicotine, quercetin, and rutin. These results show the potential of these compounds as botanical pesticides, which can be applied for the biological control of the grasshopper C. abbreviatus .